Corviale Megastructure: Narratives of Utopia and Roman Realism. Issue 3 (2nd September 2018) - Wilhelm, Hans-Christian
ABSTRACT: Corviale is a linear mass-housing complex of one km length on the outskirts of Rome (Italy), realised between 1972 and 1982. Similar to other megastructures, it underwent social decline and until recently was considered a failed experiment. Outstanding both in scale and design complexity, its genesis spans a crucial turn in the development of mass-housing and urban design. This paper analyses Corviale's development and conceptual narratives in relation to its architectural fabric. It discusses the project within the context of late modernist large-scale housing, namely the megastructure family. A critical review of the project's roots in twentieth-century Roman urban planning and architectural historiography provide insight into the conceptual shift from international avant-garde to an allegedly site-specific, Roman identity. Historiographic narratives are compared, addressing the visual versus the societal notions of the term "utopian" in relation to the project. Even before completion, architect Mario Fiorentino revisited his own project, re-proposing it as an as-found structure within a collage of other projects, in order to regain a sense of grounding within tradition, an attempt of recollection of the city within suburbia. Similarly, the term urbatecture shifted from a synonym of megastructure to an historical frame of reference.